AB0950 Leucine-Rich Alpha-2 Glycoprotein (LRG) as A Possible Urinary Marker for Lupus Nephritis. (15th July 2016) - Lee, H.; Fujimoto, M.; Hosono, Y.; Suzuki, K.; Honda, H.; Urushima, H.; Ohkawara, T.; Serada, S.; Takeuchi, T.; Mimori, T.; Naka, T.
Abstract : Background: Lupus nephritis (LN) is a serious complication of systemic lupus erythematosus (SLE). Its accurate evaluation is dependent on renal biopsy. A search for other non-invasive methods such as urinalysis is warranted. Recently, we identified a novel acute phase protein, LRG 1, 2 whose expression is induced at the site of inflammation by various inflammatory cytokines. Objectives: To investigate whether LRG can be a new urinary biomarker of LN. Methods: We determined LRG levels in serum and urine of SLE patients (n=46, M:F=3:43, age: 37.1 (22–66)) with or without LN by ELISA. We divided SLE patients into four groups according to the results of renal biopsy (group 1: no LN [n =19], group 2: LN class 5 [n =3], group 3: LN class 1 or 2 [n =4], group 4: LN class 3 or 4 [n =20] (ISN/RPS)), and analyzed the relationship between urinary LRG levels and renal pathology. Also, we analyzed NZ B/W F1 mice, a lupus model, to study the mechanism of LRG expression in LN. Mouse urinary LRG levels were determined by western blot. Also, we evaluated the expression of LRG and several cytokines in kidney by real-time PCR, immunohistochemistry (IHC) and immunofluorescence (IF). In vitro, we investigated the expression and secretion of LRG in primary tubular epithelial cells (PTEC) obtained from NZ B/W F1. Results: Urinary LRG levels were significantly higher in group 4 patients, and tend to be high in group 2 and 3 patients compared with group 1. In kidney of NZ B/W F1 mice with LN-like alteration, mRNA expression of LRG and IL-1 beta was significantly up-regulated, compared with NZ B/W F1 mice without LN-like alteration and B6 mice. By IHC and IF analysis, LRG protein was detected in renal tubular epithelia of NZ B/W F1 mice with nephritis. Additionally, macrophage infiltration and IL-1beta production was detectable around of the LRG-positive tubules in NZ B/W F1 mice. In vitro, LRG expression and secretion was induced by IL-1beta in PTEC of NZ B/W F1 mice. Conclusions: Urinary LRG may be a useful biomarker which reflects the active inflammation of LN. References: Serada S, Fujimoto M et al. iTRAQ-based proteomic identification of leucine-rich alpha-2 glycoprotein as a novel inflammatory biomarker in autoimmune diseases. Ann Rheum Dis. 69(4):770–4 (2010) Fujimoto M, Serada S et al. Leucine-rich α2 -glycoprotein as a potential biomarker for joint inflammation during anti-interleukin-6 biologic therapy in rheumatoid arthritis. Arthritis Rheumatol. 67(8):2056–60 (2015) Disclosure of Interest: None declared